SOCIAL BONDING DALAM PENGELOLAAN HUTAN RAKYAT: UPAYA MENUJU MASYARAKAT HUTAN YANG SEJAHTERA - Setiyawan, Khabib Bima (JPW (Jurnal Politik Walisongo), 2019)
The forest is the source of livelihood of the community around it, forest sustainbility management become important thing to do to ensure the sustainbility of the forest. This research discusses about forest management strategies in the Berjo village, in which consist of three different institutions, they are Taman Hutan Raya (Tahura), Perusahaan Hutan Negara Indonesia (Perhutani), and Lembaga Masyarakat Desa Hutan (LMDH). the aim of this research is to find out the forest management strategies, methode in this research is qualitaive with case studies approach, this research conducted in the village of Berjo, Karangayar city. Purposive sampling is used to select the respondents. Data collection is done by observation, interviews, and documentation. The analysis of the data using the in interactive functional analysis and validation of data using triangulation of sources. The results showed that forest management is achieved by collaboration among Government and non government institutions with their Sosial Bonding Capital which allows for interaction in sharing knowledge as well as glue relations between groups. Social Bonding is owned by LMDH and Tahura are on the intermediate level which means they obey formal but on the other hand they approach at the level of values, culture, and perception. While the relationship between the LMDH (a unit of BUMN) and Tahura (units of goverment departmen) are on the level of social capital that embraced a formalvalue corresponding their jobs desk which are conservation and production of the forest. LMDH along with Perhutani in forest management through partnership relationship. They work togehter in the safeguarding of forests and open tourist attraction. Whereas in the greening of the forest, the Perhutani, the LMDH Tahura and do reforestation.